Bioalcohol production : biochemical conversion of lignocellulosic biomass - Waldron, K. ([S.l.] : CRC Press, 2010)
Bioethanol is one of the main biofuels capable of substituting petroleum usage in vehicles, and has had one of the largest impacts to date. The first generation of bioethanol production has had a worldwide impact, though it is restricted by energy intensive grain-to-bioethanol production technology, and land usage pressures (food vs. fuel). The development of second generation production technology, producing a wider range of bioalcohols from lignocellulosic biomass, removes many of the obstacles and expenses that first generation production faces. This book provides a comprehensive and timely reference on the biochemical conversion of lignocellulosic biomass for the production of fuel alcohols, expertly reviewing the development of the entire second-generation bioalcohol production chain. The book covers the process engineering, technology, modeling, and integration of the entire production chain, from feedstock pretreatment on to hydrolysis, to fermentation, and on to purification. The book primarily covers the production of bioethanol, but extends into coverage of the production of longer-chain bioalcohols that will be elemental to future biofuel utilization.
Keywords: Lignocellulose--Biotechnology